Penguatan Kapasitas Ustadz Ustadzah TPQ Melalui Pendidikan Islam, Kesehatan Mental, dan Hukum Penguatan Kapasitas Ustadz Ustadzah TPQ Melalui Pendidikan Islam, Kesehatan Mental, dan Hukum - Ngatmin Abbas; Arif Effendi (Jurnal Medika: Medika, 2026)
This community service program aims to enhance the capacity of Qur’anic School (TPQ) teachers (ustadz/ustadzah) in educational management that is both instructive and attentive to children’s mental-spiritual health, grounded in legal aspects of child protection. The program was implemented as a workshop for TPQ teachers in Kaliancar Village, Selogiri District, Wonogiri Regency, in 2026. Two facilitators, Ngatmin Abbas, M.Pd., and Luthfi Afandi, led sessions covering enjoyable Qur’anic teaching strategies, basic understanding of child mental health, the importance of spiritual nurturing, and dissemination of child protection laws. The workshop methods included interactive lectures, group discussions, simulations, and Q&A sessions. The results indicate high enthusiasm from the 25 participants. The TPQ teachers found it helpful to learn child-friendly teaching methods, techniques to maintain students’ motivation, early detection of children’s emotional issues, and the application of noble values in TPQ activities. Quantitative feedback showed 92% of participants reported improved understanding of effective TPQ management, 88% gained new knowledge on children’s mental health, and 100% agreed that spiritual values must be integrated into teaching and learning. Participants also appreciated the information on legal aspects, especially regarding children’s rights to education and protection from violence. In conclusion, the workshop effectively increased TPQ teachers’ knowledge and awareness of child-friendly Qur’anic teaching, the importance of students’ mental and spiritual health, as well as legal responsibilities in conducting religious education.